Influence of Brevicoryne brassicae L. incidence on the yield of marketable cabbage heads under different insecticide spray regimes in highlands of Himachal Pradesh (India) (Bangladesh Journal of Botany, 2018)
Strong and negative correlation was observed between the yield of marketable cabbage heads and populations of/plant infestations by cabbage aphid (Brevicoryne brassicae L.) 14 days after first and second spray. Weak correlation existed between yield of marketable cabbage heads and aphid populations/plant infestations at pre-treatment. Therefore, insecticide sprays should be done to control late aphid infestations and avoided against early aphid infestations.